The NeuGRID Workflow: a “Swiss Army knife” for MRI processing - De Francesco, Silvia; Archetti, Damiano; Redolfi, Alberto (Alzheimer's & dementia, 2023)
Background The advent of big data and artificial intelligence has energized the neuroimaging community with powerful processing tools and the need for large‐scale computational resources for data analysis has increased. Not all neuroscientists have access to extensive resources or have sufficient expertise to configure these libraries, making them difficult to use. Method A collection of popular MRI scan processing software, (i.e.: Fsl, FreeSurfer, Ants, SPM, Adaboost, Neuromorphometrics, LPA, Tracula) was selected as a proof of concept to be included in the NeuGRID Workflow to produce an advanced tool for group analysis and biomarkers assessment. Result The NeuGRID Workflow was designed to allow the user to build a custom MRI processing pipeline by means of a layered structure (Fig.1) available for users at the URL https://neugrid2.eu/index.php/workflowgroup. In the first layer, the user must upload a compressed file containing T13D, FLAIR, and DWI scans of subjects. In the second layer, the user selects which kind of MRI sequence to process. If DICOMs were uploaded, the third layer provides tools to convert DICOMs into NIFTI, the default format for all subsequent workflow processes. All DICOMs are anonymized upon upload. The fourth layer allows the user to choose how images are preprocessed, and the preprocessing pipelines can be customized for different modalities. In the final layer, the user can choose how to analyze the images to calculate volume, thickness, area and curvature of brain regions, quantify white‐matter lesions and reconstruct major white‐matter pathways. The triggered job is efficiently parallelized using a Sun Grid Engine scheduler to reduce computation time. After the scans are processed in the NeuGRID cluster (450 CPUs, 2.5TB memory, 400TB storage), the user is notified by email that the job is finished and the results can be downloaded. Conclusion The NeuGRID Workflow is a practical tool that allows researchers without computational resources and/or expertise to design a custom pipeline to process large amounts of data from anywhere using a traditional laptop or personal computer. The collection of heterogeneous tools provides a high degree of freedom in pipeline design, making NeuGRID Workflow a Swiss Army knife for MRI processing